KONSENTRASI SENYAWA DIMETILSULFIDA (DMS) DI PANTAI UTARA JAWA BARAT DAN KEMUNGKINAN DAMPAKNYA PADA PRODUKSI UDANG - Wage Komarawidjaja (Jurnal Teknologi Lingkungan, 2006)
Shrimp culture has became one of the most important Indonesian exportcommodity since 1985 up to the beginning of 1990`s. Due to theincreasing intensification, the pressure on the shrimp ponds environmenthas became a serious problem. The problem was indicated by thedecrease in shrimp production since 1992. Dimethylsulfide (DMS) isknown as a major contributor to total sulfur emission from land and coastalmarine and also known to inhibit nitrification. In this respect, we arestudying the influence of DMS on nitrification process in saline water.This paper describes the DMS concentration observed in several places inthe Western Coast of North Java. The minimum and maximum concentrations observed were 790.32 ηM and 6483.87 ηM respectively. These figures are higher than concentration detected in any other coastal area where shrimp productions are concerned. We speculate that DMS has given some contributions in the depletion of shrimp production.